From Qibla Deviation to Social Cohesion: The Construction of Minority Fiqh at the Great Mosque of Makale, Tana Toraja - Faiz, ABD Karim; AR, Zulfahmi; Awaka, M. Qahar; Wahidin, Wahidin (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The determination of the qibla direction constitutes a normative obligation in Islamic law; however, in minority contexts, its practice often intersects with socio-cultural realities, architectural considerations, and interfaith negotiations—dimensions that remain relatively neglected in both Islamic law scholarship and contemporary legal studies. This article examines the case of the Great Mosque of Makale in Tana Toraja, whose orientation deviated by approximately 22° from the astronomical qibla between 1934 and 2020, to analyze the dynamics of minority fiqh (Islamic jurisprudence) construction in a multicultural setting. Employing a qualitative socio-historical approach through observation, document analysis, and in-depth interviews with seven key informants, the study finds that the mosque’s orientation was not solely determined by fiqh norms but emerged from a social compromise institutionalized through adat deliberations in the tongkonan, involving both Muslim and Christian leaders. This compromise was shaped by four interrelated factors: the pursuit of interreligious harmony; urban spatial aesthetics that aligned the mosque with the adjacent church; the internalization of Toraja local wisdom, such as solata’ and the principle of pa’daidi; and an early theological interpretation that prioritized a general westward orientation. The article argues that Islamic law in minority contexts does not function as a rigid, normative system, but rather as an adaptive and responsive social construction grounded in the maqāṣid al-sharīʿah (objectives of Islamic law). Accordingly, the qibla deviation in Makale should not be understood as a religious aberration but rather as an existential strategy through which Muslims sustain social cohesion and affirm collective identity within a predominantly non-Muslim society. [Penentuan arah kiblat merupakan kewajiban normatif dalam syariat Islam, namun dalam konteks masyarakat minoritas praktik tersebut kerap berhadapan dengan realitas sosial-budaya, pertimbangan arsitektural, dan negosiasi lintas agama yang jarang disentuh dalam kajian fikih maupun studi hukum kontemporer. Artikel ini mengkaji kasus deviasi arah kiblat Masjid Agung Makale di Tana Toraja, yang sejak 1934 hingga 2020 menyimpang sekitar 22° dari presisi astronomis, dengan tujuan menganalisis dinamika konstruksi fikih minoritas dalam masyarakat multikultural. Penelitian menggunakan metode kualitatif dengan pendekatan sosio-historis melalui observasi, analisis dokumen, dan wawancara mendalam terhadap tujuh informan kunci. Temuan menunjukkan bahwa orientasi masjid tidak semata-mata ditentukan oleh norma fikih, melainkan merupakan hasil kompromi sosial yang dilembagakan melalui musyawarah adat di tongkonan dengan melibatkan tokoh Muslim dan Kristen. Kompromi tersebut terwujud dalam empat faktor utama: upaya menjaga kerukunan antar umat beragama, pertimbangan estetika tata ruang kota yang menyelaraskan masjid dengan gereja, internalisasi kearifan lokal solata’ dan prinsip pa’daidi, serta pemahaman teologis yang fleksibel pada masa awal. Artikel ini berargumen bahwa hukum Islam dalam ruang minoritas tidak hadir sebagai sistem normatif yang rigid, melainkan sebagai konstruksi sosial yang adaptif, responsif, dan berorientasi pada maqāṣid al-sharīʿah. Dengan demikian, deviasi arah kiblat di Makale tidak dapat dipahami sebagai penyimpangan keagamaan, melainkan sebagai strategi eksistensial umat Islam untuk merawat kohesi sosial sekaligus meneguhkan identitas kolektif dalam struktur masyarakat yang didominasi kelompok non-Muslim.]